Wenfei Buqi Tongluo Formula Against Bleomycin-Induced Pulmonary Fibrosis by Inhibiting TGF-β/Smad3 Pathway - Ding, Lu; Li, Yaxin; Yang, Yingying; Song, Siyu; Qi, Hongyu; Wang, Jing; Wang, Ziyuan; Zhao, Jiachao; Zhang, Wei; Zhao, Linhua; Zhao, Daqing; Li, Xiangyan; et al. (Frontiers in Pharmacology, 2022)
Pulmonary fibrosis (PF) is the end-stage of various chronic and progressive interstitial lung diseases. TGF-β, a profibrotic cytokine, can promote epithelial-mesenchymal transition (EMT), extracellular matrix (ECM) accumulation, and fibroblast proliferation, which contribute to progressive lung remodeling in PF. The Wenfei Buqi Tongluo (WBT) formula, has been certified to be effective in the prevention and treatment of PF in clinical practice and has inhibitory effects on EMT, inflammation, and profibrotic factors. However, the pharmacological mechanisms of WBT against PF need to be further explored. In this study, we first analyzed the chemical components of the WBT formula using the UHPLC/Q-TOF-MS analysis. The potential targets of the identified compounds from WBT were predicted by network pharmacology, which was confirmed by in vivo and in vitro study. After screening by the PubChem database, we first identified the 36 compounds of WBT and predicted the TGF-β signaling pathway, with ECM degradation as potential mechanism of WBT against PF by network pharmacology. Furthermore, WBT treatment inhibited the levels of TGF-β and Smad3 phosphorylation, and subsequently alleviated EMT and ECM accumulation in the bleomycin-induced mouse model and TGF-β1-induced cell model. These findings indicate that WBT can block the progressive process of PF by inhibiting EMT and promoting ECM degradation via the TGF-β/Smad3 pathway. This study may provide new insights into the molecular mechanism of WBT for the prevention and treatment of PF in clinical application.